Human Immunodeficiency Virus Type-1 (HIV-1) Transcriptional Regulation, Latency and Therapy in the Central Nervous System - Joseph Hokello; Adhikarimayum Lakhikumar Sharma; Priya Tyagi; Alok Bhushan; Mudit Tyagi (Vaccines, 2021)
The central nervous system (CNS) is highly compartmentalized and serves as a specific site of human immunodeficiency virus (HIV) infection. Therefore, an understanding of the cellular populations that are infected by HIV or that harbor latent HIV proviruses is imperative in the attempts to address cure strategies, taking into account that HIV infection and latency in the CNS may differ considerably from those in the periphery. HIV replication in the CNS is reported to persist despite prolonged combination antiretroviral therapy due to the inability of the current antiretroviral drugs to penetrate and cross the blood–brain barrier. Consequently, as a result of sustained HIV replication in the CNS even in the face of combination antiretroviral therapy, there is a high incidence of HIV-associated neurocognitive disorders (HAND). This article, therefore, provides a comprehensive review of HIV transcriptional regulation, latency, and therapy in the CNS.